Genotypic modulation of nanoparticles-induced tolerance in heavy metals-stressed crops; a literature review - Hammad, Muhammad; Riaz, Aasma; Chouhdary, Laraib; Kabir, Muhammad; Rios-Escalante, Patricio R. De los (Frontiers in Plant Science, 2026)
To address the limited understanding of genotypic responses mediated by nanoparticles under heavy metal stress, this review summarizes research on “Genotypic Modulation of Nanoparticles-Induced Tolerance in Heavy Metals-Stressed Crops”. Topics covered include heavy metal toxicity in agriculture, including global prevalence and impacts on crop yield, soil health, and food safety; current mitigation strategies and their limitations; nanoparticles as a novel solution with unique properties and examples; research gaps focusing on physiological effects versus genotypic diversity; and review objectives focusing on NP-induced genotypic modulation and proposing a nano-genomic approach integrating omics tools. The review’s objectives were to compare physiological and genotypic crop responses, assess the effects of heavy metal toxicity, benchmark mitigation techniques, describe the functions of nanoparticles, and suggest an integrated nano-genomic framework. Relevant research from around the world was examined, with a focus on multi-omics techniques and the use of nanoparticles in a variety of crops. The results show that while genotypic variation affects tolerance mechanisms mediated by differential gene expression and epigenetic regulation, nanoparticles outperform conventional methods in improving physiological traits, reducing metal uptake, and enhancing antioxidant defenses. Although multi-omics integration clarifies the intricate molecular networks that underlie the reduction of stress caused by nanoparticles, it is still constrained by methodological heterogeneity and insufficient data synthesis. Even though nanoparticle properties and application methods have a significant impact on efficacy, further study is required to ascertain long-term impacts and environmental safety. Despite significant properties and application methods, still it required more study and research for long-term impacts and environmental safety and sustainability. Altogether, it will contribute to novel nano-genomic strategies for constraining sustainable crop resilience against heavy metal contamination.